2021
DOI: 10.48550/arxiv.2105.05071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accelerating Amoebots via Reconfigurable Circuits

Michael Feldmann,
Andreas Padalkin,
Christian Scheideler
et al.

Abstract: We consider an extension to the geometric amoebot model that allows amoebots to form so-called circuits. Given a connected amoebot structure, a circuit is a subgraph formed by the amoebots that permits the instant transmission of signals. We show that such an extension allows for significantly faster solutions to a variety of problems related to programmable matter. More specifically, we provide algorithms for leader election, consensus, compass alignment, chirality agreement and shape recognition. Leader elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…In this paper, we assume that all amoebots share a common compass orientation and chirality. This is reasonable since Feldmann et al [7] showed that all amoebots are able to come to an agreement within the considered extension (see Section 1.4).…”
Section: Geometric Amoebot Modelsupporting
confidence: 77%
See 4 more Smart Citations
“…In this paper, we assume that all amoebots share a common compass orientation and chirality. This is reasonable since Feldmann et al [7] showed that all amoebots are able to come to an agreement within the considered extension (see Section 1.4).…”
Section: Geometric Amoebot Modelsupporting
confidence: 77%
“…In the reconfigurable circuit extension [7], each edge between two neighboring amoebots u and v is replaced by k edges called external links with endpoints called pins, for some constant k ≥ 1 that is the same for all amoebots. For each of these links, one pin is owned by u while the other pin is owned by v. In this paper, we assume that neighboring amoebots have a common labeling of their incident external links.…”
Section: Reconfigurable Circuit Extensionmentioning
confidence: 99%
See 3 more Smart Citations